ANALISIS PEMANFAATAN PLATFORM RUANG GTK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR :SYSTEMATIC LITERATURE REVIEW - oktaviani, Revani; Dian Rahadian; Yuniar Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to systematically review the literature on the use of GTK Rooms and their impact on the pedagogical competence of elementary school teachers, as well as the supporting and inhibiting factors. Articles were selected based on the Systematic Literature Review (SLR) method with reference to the PRISMA protocol, and from the results of a search in the Google Scholar database, eight articles from 2020 to 2025 were obtained. From the results of the study, it can be concluded that GTK Rooms are very influential in improving pedagogical competence, particularly in designing technology-based learning and evaluation using digital assessment. There are also several major challenges, including limited internet access, lack of digital literacy skills, especially among senior teachers, and lack of pedagogical technical assistance when the material is applied. The GTK Room has the potential to be a strategy for improving the pedagogical competence of elementary school teachers, but this needs to be accompanied by a more comprehensive approach, such as infrastructure improvements, ongoing mentoring, and the development of professional communities within the learning platform.